MODELS AND APPROACHES OF CONTINUOUS PROFESSIONAL DEVELOPMENT (The Role of Exact Sciences in the Era of Modern Development, 2024)
The article discusses various models and approaches of Continuous Professional Development (CPD) for teachers, such as Communities of Practice, Action Research, Collaborative Inquiry, and Job-Embedded Professional Learning. These approaches emphasize collaboration, reflective practice, and alignment with teachers' needs and classroom realities. The challenges and barriers to effective CPD include time constraints, inadequate resources, lack of support from school leadership, and insufficient follow-up. The perception of CPD as a top-down process, as well as ambiguity regarding its definition and scope, further complicates its implementation. The text underscores the importance of tailored and sustained CPD efforts that focus on teachers’ individual needs and experiences to enhance student outcomes and teacher efficacy.